Traditional Ritual of Karue Ase: Local wisdom and cultural conservation in the Labian Ira'ang Society - Adriana Gandasari; Markus Iyus Supiandi; Didin Syafruddin; Serafin Tanti Nita; Mawardi Mawardi (JPBIO (Jurnal Pendidikan Biologi), 2022)
Karue Ase's traditional rituals to the people in Labian Ira'ang have been performed for generations, but they are delivered orally from generation to generation and have never been documented and published. The purpose of this study is to document and describe the traditional rituals of Karue Ase in the Labian Ira'ang community. This study uses survey methods. Data collection uses in-depth interview sheets and field observations. Data analysis uses qualitative descriptive analysis. The results showed that the people in Labian Ira'ang used plants, animals, and stones to perform Karue Ase rituals. The plants used are Piper betle L., Areca catechu L., Uncaria gambir (Hunter) Roxb., Nicotiana tabacum L., and Cocos nucifera L. Types of animals used among others Cervus unicolor, Pilsbryoconcha exilis, and Rasbora sp. The types of stones used are Panulung stone, Lanying stone, Kait stone, and Baram stone.